Design of an Air Suction Wheel-Hole Single Seed Drill for a Wheat Plot Dibbler - Xinchun Ma; Qixiang Gong; Qingjie Wang; Dijuan Xu; Yinggang Zhou; Guibin Chen; Xinpeng Cao; Longbao Wang (Agriculture, 2022)
Focusing on the problems of the poor filling ability and stability of the mechanical wheat seeder and the complicated structure of the pneumatic seeder, a special air suction wheel-hole single seed drill for remote controlled self-propelled single seed dibbler in wheat plots was designed in this paper. According to the agronomic requirements of precision seeding in wheat plots, the seeding wheel radius was set at 180 mm 16 suction holes. Using the discrete element simulation software EDEM to analyze the seed disturbance effect of different parameter designs, the thickness of seed suction ring was 16 mm, the height of seed suction mouth was 4.5 mm, and the diameter of seed suction cam was 12 mm. Through hydrodynamic simulation, the phase angle of the negative pressure chamber was 280 degrees, positive pressure chamber was 22 degrees, phase angle of the unpressurized interval zone was 20 degrees, thickness of the negative pressure chamber was 24.5 mm, diameter of transition pipe was 17.5 mm and length of the transition pipe was 14.5 mm. Based on the above design parameters, the samples were then processed and benchtop experiments carried out. The results showed that under the best operating parameters, the re-suction index was 0.82%, the leakage index was 6.67%, and the qualified index was 92.41%, which met the design requirements. This study could provide a reference for the design of single-seed dibbling technology in wheat plots.